Colemanite: A Fire Retardant Candidate for Wood Plastic Composites - Terzi, Evren; Kartal, Saip Nami; Piskin, Sabriye; Stark, Nicole; Figen, Aysel Kanturk; White, Robert H. (NORTH CAROLINA STATE UNIV DEPT WOOD & PAPER SCI, 2018)
The use of raw boron minerals (i.e. tincalconite, colemanite, and ulexite) was evaluated to increase the fire performance of wood plastic composites (WPCs) in comparison with commercially available fire retardants (FRs). Cone calorimetry and limited oxygen index tests were performed to evaluate the fire properties of WPC specimens. Artificial weathering and 3-point bending tests were also performed on the test specimens loaded with the highest loading level of FRs. The most important decrease in the heat release rate values was 42% and 40% in the magnesium hydroxide-and colemanite-added WPCs at a loading level of 15% (w/w), respectively. Incorporation of colemanite and ulexite into the WPCs increased the limited oxygen index levels by nearly 13% at the same loading level. An increase was observed in the peak heat release rate values in all of the WPC specimens after accelerated weathering. All of the FRs had statistically improved MOE values compared with the control WPC specimens. In particular, the incorporation of zinc borate and borax increased the MOE values by approximately 48% and 42%, respectively. Similar to the effect on the MOE values, zinc borate and borax improved the modulus of rupture the most (approximately 18%).
Keywords: WPC; Raw boron minerals; Cone calorimeter; Limited oxygen index; Artificial weathering; DENSITY POLYETHYLENE COMPOSITES; CONE CALORIMETER DATA; THERMAL-DEGRADATION; FIBER COMPOSITES; FLAMMABILITY; NANOCLAY; Materials Science